COMPARATIVE PERFORMANCE OF GROWTH IN DIPLOID AND TRIPLOID TURBOT (Scophthalmus maximus L.) - Fernández-Pato, Carlos; Martínez-Tapia, Inmaculada; Vázquez, Emilia; Blanco, Gloria; Sánchez, José Antonio (2013)
In this experiment two groups (diploid and triploid individua of turbot (Scophthalmus mo.ximus L.) have been studied, kept under the same conditions of culture, over a period of 6 months. Along this period of time, growth rates did not show significant differences in tiheir behaviour (p=0.1 Pillais test, for N=285) after applying a multivariate analysis of variance (MANOVA) with a design of repeated measures. Similarly, the survival rates in this iwo groups did not show significant differences (p >0.05) according to the actuarial method (Lee & Desu test). No